Study Experimental of Temperature Effect of B40 Biodiesel Engine Performance - Dwiki Wisnu; Romy Romy (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2023)
This paper aims to determine the performance of diesel engine and increase the injection pressure by varying the fuel temperature using biodiesel B40 with a compression ratio of 21:1 and an injection pressure of 150 Bar. The parameters were calculated include, h at the orifice, the volume of fuel used, fuel consumption time, and engine rpm. In the tests carried out, it was found that variations in fuel temperature affect engine performance parameters such as effective shaft power, average effective pressure, thermal efficiency values, air fuel ratio, and specific fuel consumption. The results of the fuel temperature test with variations of 50oC, 55oC, 60oC, 65oC and 70oC. Where for the value of the largest effective shaft power at a temperature of 60oC with a value of 3.7892 kW at a load of 25,000 kg/m2 and the largest BMEP (Brake Mean Effective Pressure) at a temperature of 70oC with a value of 1275.321 N/m2, for the value of thermal efficiency, specific fuel consumption, ratio of air and the best fuel at a temperature of 65oC with a thermal efficiency value of 92.333 % at a load of 25,000 kg/m2, for a better air-fuel ratio with a value of 157,660 at a load of 5,000 kg/m2, and the smallest specific fuel consumption with value 0.00002291 kg/kJ at a load of 25,000 kg/m2.